EFFECT OF ERYTHROPOIETIN ON CYTOKINE PRODUCTION BY STEM CELLS - A. P. Lykov; M. A. Surovtseva; O. V. Poveshchenko; N. A. Bondarenko; I. I. Kim; A. M. Chernyvski; A. V. Fomichev (Медицинская иммунология)
Erythropoietin (EPO) is mainly used to stimulate erythropoiesis. Its cytoprotective effects upon other cells of the human body and animals were recently shown, in particular, anti-apoptotic effect was observed. EPO effect upon the cells is mediated by interaction with erythropoietin receptor, with a complex forming a heterodimeric bond with β-common chain (CD131). In the present work, we studied the changes in erythropoietin receptor expression, and production spectrum of biologically active molecules in bone marrow mononuclear cells (BM-MNC) of patients with coronary heart disease. The flow cytometric assays showed that short-term incubation of BM-MNC with erythropoietin caused increased expression of the erythropoietin receptors on hematopoietic stem cells and tended to reduce the number of endothelial progenitor cells carrying the erythropoietin receptors. Solid-phase enzyme immunoassay in conditioned media from BM-MNC revealed that long-term (72 hours) exposure of BM-MNC to erythropoietin promoted increased production of IL-1β, PDGF-AB, and Epo, if compared to the basal production level (p < 0.05). Short-term incubation of BM-MNC with erythropoietin (60 minutes) caused a significant increase in the IL-1β, PDGF-AB and CXCL-12 / SDF-1α production levels, as well as significant reduction in the IL-10 production levels compared to the basal levels (p < 0.05).